2018
DOI: 10.1186/s12955-018-0935-6
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural adaptation and validation of the Italian version of the Hip disability and Osteoarthritis Outcome Score (HOOS)

Abstract: ObjectiveTo create a translated version of the HOOS to fit the Italian population and to test its psychometric properties and validity in hip osteoarthritis (OA) patients undergoing total hip arthroplasty (THA).DesignThe HOOS Italian version was developed according to published international guidelines that include preparation, forward translation and reconciliation, backward translation, review and harmonization, and proof reading. The Italian HOOS was administered to 145 patients (mean age 65.7 ± 11.6 years,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 31 publications
6
11
0
Order By: Relevance
“…A lower value of alpha could be due to a heterogeneous construct of these subscales. Cronbach's alpha was greatest for the ADL subscale both preoperatively and at follow-up (0.95 and 0.97 respectively), which concurs with previous validation studies (0.94 in the French version, and 0.98/0.95 for OA/THR group in the Dutch version [23], 0.96 in the Korean [38], German [37] and Italian [45] versions and 0.97 in the Japanese version [42]. However, since it had been reported [46,47] that subscales showing a high coefficient alpha are not necessarily homogenous or unidimensional, very high Cronbach's alpha (exceeding 0.9) may suggest that some items of both, the 17-item ADL Function subscale, and the 10-item Pain subscale are redundant as they test the same question in a different guise.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A lower value of alpha could be due to a heterogeneous construct of these subscales. Cronbach's alpha was greatest for the ADL subscale both preoperatively and at follow-up (0.95 and 0.97 respectively), which concurs with previous validation studies (0.94 in the French version, and 0.98/0.95 for OA/THR group in the Dutch version [23], 0.96 in the Korean [38], German [37] and Italian [45] versions and 0.97 in the Japanese version [42]. However, since it had been reported [46,47] that subscales showing a high coefficient alpha are not necessarily homogenous or unidimensional, very high Cronbach's alpha (exceeding 0.9) may suggest that some items of both, the 17-item ADL Function subscale, and the 10-item Pain subscale are redundant as they test the same question in a different guise.…”
Section: Discussionsupporting
confidence: 90%
“…As expected, we found strong correlations between subscales of the HOOS and SF-36 that were intended to measure similar constructs. The correlation values were comparable to those reported by de Groot et al [23], Satoh et al [42] and Torre et al [45] in THR patients with a mean age of 62-66 years and higher than observed by Nilsdotter et al in Swedish patients over 70 years of age [4]. This observation might have been expected since the outcome in THR is not specific to the joint but to overall impact on health, and therefore sensitive to age.…”
Section: Discussionsupporting
confidence: 87%
“…One questionnaire (Euro Quality 5 Dimensions, EQ-5D-3 L) for the general assessment of the patient health status will be administered to all patients enrolled in the study [21]. According to the surgical procedure, patients will be administered with a joint-specific questionnaire: the Hip disability and Osteoarthritis Outcome Score – Physical function Short-form (HOOS-PS) for patients undergoing hip replacement [22]; the Knee injury and Osteoarthritis Outcome Score – Physical function Short-form (KOOS-PS) for patients undergoing knee replacement [23]; the American Shoulder and Elbow Surgeons Standardized Shoulder Assessment Form (ASES), for patients undergoing shoulder implants. This last questionnaire will be administered in a modified version that does not include the assessments performed by the orthopedic surgeon [24].…”
Section: Methodsmentioning
confidence: 99%
“…The 5 items included in the short form measure physical function and are rated on five-point Likert scale (none, mild, moderate, severe, extreme), where 0 indicates no problems and 4 extreme problems. Item score can be transformed to a 0–100 scale with 0 indicating the worst problems and 100 indicating no problems The HOOS was translated and adapted to Italian, according to the international guidelines provided by Torre et al [22].…”
Section: Methodsmentioning
confidence: 99%
“…The HOOS was developed in 2003 by the Swedish researchers to extend the WOMAC [20,21,22] and to evaluate the patients’ view about their hip dysfunctions. The HOOS questionnaire has been developed, validated, and translated into several languages (Chinese, Dutch, French, German, Italian, Japanese, Korean, Persian, Spanish, Thai), which makes the opportunity to conduct international, multicenter studies [20,21,23,24,25,26,27,28]. Questionnaires are available to download free of charge from .…”
Section: Introductionmentioning
confidence: 99%